Terrain Evaluation of the Dempster Highway across the Eagle Plain and along the Richardson Mountains, Yukon Territory - Richardson, Neil W.; Sauer, E. Karl (Canadian Geotechnical Journal, 1975)
A detailed terrain classification was carried out as part of a study on the Dempster Highway from Mile 166 to Mile 290.5, the Yukon–Northwest Territories Border. The objective was to establish a rational basis for field testing and subsurface exploration programs in the future and the evaluation of the potential effects upon the physical environment of the construction of highways and other transportation facilities in the Arctic, on terrain composed of sedimentary rocks which have not been glaciated. Terrain units were established on the basis of geology, vegetation, topography, and patterned ground. The subsurface sediments were mapped mainly as outcrops of weathered shale and sandstone. The sandstone was found to be the most stable foundation and borrow material. The shale was found to be mainly clay with high ice contents near the surface, and was observed to be very unstable when thawed. A number of plant communities, which differed significantly from a geotechnical point of view, were identified.